2022
DOI: 10.5435/jaaosglobal-d-21-00203
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of the Cost and Efficacy of Intra-Articular Knee Injections

Abstract: Introduction: Intra-articular joint injections have been used with the goal of providing patients with symptomatic relief. Recently, however, the efficacy of corticosteroid (CS) and hyaluronic acid (HA) injections in the management of knee osteoarthritis (OA) is questionable. In this analysis, we investigated the costs associated with injections by assessing overall use, conversion and average time to total knee arthroplasty (TKA), and reimbursement. Methods: Patients aged 50 to 70 years with a knee-related di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 30 publications
0
2
0
Order By: Relevance
“…One analysis found that while both corticosteroids and HA reduced the risk of surgery for patients within 10 years, the risk of surgery and the cost of treatment were slightly higher in the HA cohort than in the It should be noted that the efficacy of HA is limited. One analysis found that while both corticosteroids and HA reduced the risk of surgery for patients within 10 years, the risk of surgery and the cost of treatment were slightly higher in the HA cohort than in the corticosteroid cohort [36]. Another clinical trial found that corticosteroids and HA were able to alleviate OA progression, but patients treated with HA injections were at a higher risk of total knee replacement [37].…”
Section: Therapeutic Effects Of Hydrogelsmentioning
confidence: 99%
See 1 more Smart Citation
“…One analysis found that while both corticosteroids and HA reduced the risk of surgery for patients within 10 years, the risk of surgery and the cost of treatment were slightly higher in the HA cohort than in the It should be noted that the efficacy of HA is limited. One analysis found that while both corticosteroids and HA reduced the risk of surgery for patients within 10 years, the risk of surgery and the cost of treatment were slightly higher in the HA cohort than in the corticosteroid cohort [36]. Another clinical trial found that corticosteroids and HA were able to alleviate OA progression, but patients treated with HA injections were at a higher risk of total knee replacement [37].…”
Section: Therapeutic Effects Of Hydrogelsmentioning
confidence: 99%
“…corticosteroid cohort [36]. Another clinical trial found that corticosteroids and HA were able to alleviate OA progression, but patients treated with HA injections were at a higher risk of total knee replacement [37].…”
Section: Hydrogel Implantation In Jointsmentioning
confidence: 99%
“…A 2022 retrospective analysis of a national claims database investigated time to TKA after CSI or HAI. 3 Patients who underwent an intra-articular knee injection on the same day as a diagnostic code for knee-related pain, effusion, or OA (n5141,574) were compared with patients with the same knee-related diagnostic codes without a history of intra-articular knee injection (n5637,112). Eligible patients were 50 to 70 years old at the time of their first injection or knee-related diagnosis.…”
mentioning
confidence: 99%
“…Osteoarthritis continues to be a prevalent issue causing joint pain and dysfunction, with knee osteoarthritis affecting >9 million adults and costing the health care system $27 billion annually in the United States. 25 Intra-articular (IA) injection of corticosteroids is commonly performed for the nonoperative management of joint arthritis. 34 Two of the most commonly used corticosteroids for therapeutic IA injection are methylprednisolone acetate (MP) and triamcinolone acetonide (TA).…”
mentioning
confidence: 99%